2012
DOI: 10.1016/j.jfma.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intrathecal drug delivery system for refractory cancer pain patients: A single tertiary medical center experience

Abstract: Intrathecal morphine delivery by using totally implantable programmable IDDS is an effective method to relieve refractory cancer pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Despite a significant body of literature supporting the utilization of IDDS in cancer pain, worldwide utilization of this treatment modality remains relatively low when compared to the number of patients who would potentially benefit (3,18,19). In a randomized prospective study, IDDS showed improved pain scores, decreased toxicity, and increased survival when compared to conventional medical management (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a significant body of literature supporting the utilization of IDDS in cancer pain, worldwide utilization of this treatment modality remains relatively low when compared to the number of patients who would potentially benefit (3,18,19). In a randomized prospective study, IDDS showed improved pain scores, decreased toxicity, and increased survival when compared to conventional medical management (3).…”
Section: Discussionmentioning
confidence: 99%
“…IDDS has been shown to effectively reduce pain scores with better pain control and fewer adverse side‐effects after both 4‐ and 12‐week postimplantation, and has been associated with increased survival after six months . Another study found that pain scores decreased from 10 to 3.5 with administration of intrathecal analgesia, with patients showing functional improvements at 14 days with significant improvements in pain control and quality of life . IDDS has also been associated with reduced opioid toxicity, with one study demonstrating a 50% decrease in toxicity for IDDS patients compared to a 17% reduction in those with conventional pain management such as opioids .…”
Section: Introductionmentioning
confidence: 99%
“…In our series, the mean value on the visual analogue scale before the start of intrathecal infusion therapy was 7.78 ± 1.64 points, and this score is similar to that reported in other studies focussing on efficacy (Table 4). 5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] The comparison of VAS values before implantation with those 4 weeks after implantation (3.02 ± 2.44) represents a decrease of 4.75 ± 3.03 points. This decrease in the VAS scale after the first month after implantation is also similar to that published in most scientific articles, although it is a less studied aspect.…”
Section: Discussionmentioning
confidence: 99%
“…For end-of-life patients with refractory pain, this system may provide profound analgesia with minimal side effects and allow patient care on an outpatient basis. Lin et al 16 confirmed that a totally implantable programmable drug delivery system was an attractive option for managing refractory cancer pain and could provide reliable long-term analgesia without permanent nerve or plexus destruction. Compared with other methods, we regard this epidural bupivacaine-morphine infusion system as the most efficient for pain relief.…”
Section: Discussionmentioning
confidence: 99%